Natural Dog Care - Fogle, Bruce Dr. (1999)
An holistic approach to dog care is explained in this book which is backed by sound principles and practices of veterinary training. It shows that dogs respond to the environment in which they are raised and suggests that many behavioural and medical are attributable to an "unnatural" lifestyle